Baseline circulating stem-like cells predict survival in patients with metastatic breast Cancer - Lee, Chun-Hui; Hsieh, Jason Chia-Hsun; Wu, Tyler Min-Hsien; Yeh, Ting-Shiuan; Wang, Hung-Ming; Lin, Yung-Chan; Chen, Jen-Shi; Lee, Chia-Lin; Huang, Wen-Kuan; Hung, Tsung-Min; Yen, Tzu-Tsen; Chan, Sheng-Chieh; et al. (BMC cancer, 2019)
Circulating tumor cells (CTCs) are associated with breast cancer prognosis. Research is limited regarding the role of circulating cancer stem-like cells (cCSCs) considering the treatment response and survival among patients with metastatic breast cancer. Accordingly, we performed this prospective study to clarify the prognostic significance of baseline cCSCs for metastatic breast cancer in terms of first-line chemotherapy. Between April 2014 and January 2016, we prospectively enrolled 48 patients with stage IV breast invasive ductal carcinoma who underwent first-line chemotherapy. We identified and analyzed CTCs and cCSCs by using a protocol based on negative selection and flow cytometry before chemotherapy. CTCs were identified as EpCAM Hoechst CD45 cells and cCSCs as CD133 EpCAM Hoechst CD45 cells. cCSCs were expressed as a percentage of CTCs. The associations between CTCs, cCSCs, and the clinicopathological variables that were predictive of the treatment response and survival outcome were analyzed using univariate and multivariate analyses. We identified CTCs in all the enrolled patients, with a median number of 33.9/mL CTCs. CSCs were isolated in 97.9% of the patients; the median percentage of cCSCs was 14.7%. A high baseline level of cCSCs was correlated with an inferior tumor response rate (54.2% vs. 95.8%, p < 0.001), overall survival (OS; median: 27.7 months vs. not reached, p < 0.001), and progression-free survival (PFS; median: 5.7 vs. 18.0 months, p < 0.001). Multivariate analysis revealed that along with other clinical variables, baseline cCSCs remained an independent prognostic factor for OS and PFS. Baseline cCSCs predict the treatment response as well as survival in patients with metastatic breast cancer undergoing first-line chemotherapy. Therefore, the measurement of cCSCs may assist in identifying early cancer treatment response and prognosis.